New class of Proca interactions - de,Rham C; Pozsgay,V (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2020)
We propose a new class of Proca interactions that enjoy a nontrivial constraint and hence propagates the correct number of degrees of freedom for a healthy massive spin-1 field. We show that the scattering amplitudes always differ from those of the Generalized Proca. This implies that the new class of interactions proposed here are genuinely different from the Generalized Proca and there can be no local field redefinitions between the two. In curved spacetime, massive gravity is the natural covariantization, but we show how other classes of covariantizations can be considered.